2008
DOI: 10.1111/j.1742-7843.2008.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

EP4 and EP2 Receptor Subtypes Involved in Colonic Secretion in Rat

Abstract: Abstract:The study was designed to determine the prostaglandin EP receptor subtypes functionally involved in electrogenic ion secretion in rat colon. With 30 rats, measurements of short circuit current (SCC) and slope conductance were obtained by Ussing chamber technique. Prostaglandin E2 (PGE 2 ) and other EP receptor selective agonists were employed on stripped rat colon pre-treated with indomethacin and theophylline. Receptor-specific agonists were butaprost (EP 2 ), sulprostone (EP 1 and EP 3 ) and PGE 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…This fits with findings in the human duodenum using the same experimental technique [19]. Similar mechanisms appear to be present in rat colon, but in contrast to rats, where EP4 is the major mediator of the PGE 2 response [21], the human colon PGE 2 -induced secretion seems to be induced by all four receptor subtypes, EP4, EP2 and EP1/EP3, Figure 4. This underlines the notable difference of functional EP receptors in some animals as compared to man.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This fits with findings in the human duodenum using the same experimental technique [19]. Similar mechanisms appear to be present in rat colon, but in contrast to rats, where EP4 is the major mediator of the PGE 2 response [21], the human colon PGE 2 -induced secretion seems to be induced by all four receptor subtypes, EP4, EP2 and EP1/EP3, Figure 4. This underlines the notable difference of functional EP receptors in some animals as compared to man.…”
Section: Discussionsupporting
confidence: 84%
“…Indomethacin was always added 15 minutes prior to the addition of EP receptor agonists in order to minimize tissue prostaglandin production. Choices of concentration for the various drugs were based on experience from previous studies [18,21]. Bumetanide was added after EP agonist experiments on the biopsies had been completed.…”
Section: Methodsmentioning
confidence: 99%
“…PGE 2 function in the gastrointestinal tract has been well studied in relation to its receptors EP 1 , EP 2 , EP 3 , and EP 4 . In particular, EP 2 and EP 4 , which are coupled to the cAMP pathway, mediate PGE 2 -evoked colonic secretion, but not EP 1 and EP 3 , which are coupled to an intracellular Ca 2ϩ pathway (35). In this study, we have shown that a PGE 2 receptor subtype, EP 4 , is involved in AITC-evoked anion secretion in both human and rat colon (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…The PGE 2 receptor EP family includes four subtypes, and EP 2 and EP 4 receptors are involved in colonic anion secretion (35). Selective antagonists for EP 1 and EP 2 (AH6809) and for EP 4 (ONO-AE3-208) were used to investigate whether AITC-evoked anion secretion was mediated by EP receptors.…”
Section: Effect Of Ep Receptor Antagonists On Aitc-evoked Anion Secrementioning
confidence: 99%
“…9 In past few years, there have been number of studies exerting the importance of EP-4 receptor in carcinogenesis. 9 Extensive studies have been conducted on animal models of colon can cer [12][13][14] and various studies also support its role in breast cancer metastasis. [15][16][17][18] However, very few highly potent antagonists are presently available for preclinical and clinical assessment.…”
mentioning
confidence: 99%